Taxonomic revision of Entomobrya Rondani, 1861 (Collembola: Entomobryidae: Entomobryinae) from the Brazilian Amazon - Viana, Stéphanie Dos Santos; Morais, José Wellington De; Cipola, Nikolas Gioia (Zootaxa, 2024)
Herein, the species of Entomobrya Rondani from the Brazilian Amazon are reviewed. Entomobrya paroara Arlé & Guimarães, E. egleri Arlé & Guimarães and E. uambae Arlé are redescribed with neotypes designated, and their dorsal macrochaetotaxy is revealed for the first time. In addition, six new species are described: E. acreanenis sp. nov., E. albitrigona sp. nov., E. bicyana sp. nov., E. elizeuli sp. nov., E. idenilzae sp. nov. and E. pseudomaculata sp. nov. All these species from the Brazilian Amazon (except E. bicyana sp. nov.) share the prelabral chaetae smooth and bifurcate, an exclusive feature seen only in these taxa within the genus. Furthermore, E. linda Soto-Adames is herein recorded for the first time in Brazil. A new interpretation for the dorsal chaetotaxy of the genus is also provided, which includes for the first time the head postembryonic development for Entomobrya. After our revision, the number of Entomobrya species recorded in Brazil increased from 15 to 22 species, with 17 of them endemic to the country, and the genus is now registered in 18 Brazilian states, including all states which comprise the Amazon biome. Finally, an identification key for the 22 Entomobrya species recorded in Brazil is provided.